Socio-Cultural Values of Early Childhood Parenting (Ethnographic Research on Bugis Makassar South Sulawesi) - Musi, Muhammad Akil; Syamsuardi, Syamsuardi (Indonesian Journal of Early Childhood Education Studies, 2017)
This research aimed was to determine the socio-cultural values of early childhood parenting in families Bugis Makassar. The study was conducted in the form of ethnographic studies by focusing on the care of children in a family environment. Data collected through participant observation, interviews focused, and documentation of ethnographic records. The data were then analyzed using a model of the domain analysis and time series. The results showed that the family Bugis Makassar South Sulawesi still adhere to a number of socio-cultural values of care as the values considered important to be preserved and handed down in early childhood parenting.